Synthesis, Characterization and Swelling Characteristics of Graft Copolymerized Isotactic Polypropylene Film. (13th May 2010) - Sehgal, Teena; Rattan, Sunita
Abstract : Grafted membranes were prepared through chemical graft copolymerization of methyl methacrylate (MMA) onto isotactic polypropylene film (IPP). The IPP films were grafted with MMA molecules resulting in IPP-g-MMA grafts using benzoyl peroxide as an initiator in an inert nitrogen atmosphere. Using this method, the degree of grafting and morphology could be controlled through the variation of reaction parameters such as initiator concentration, monomer concentration, reaction time, and the reaction temperature. Optimum conditions pertaining to maximum percentage of grafting (%G) were evaluated as a function of these parameters. Maximum percentage of grafting (50%) was obtained at[ BPO ] = 0.03  M, [ MMA ] = 10 % V/V, and [Reaction Temperature] =70 ∘ C in a [Reaction time] of 120 minutes. IPP-g-MMA films were investigated for their swelling behavior. Water-swelling analysis of IPP-g-MMA was carried out as a function of different percentage of grafting, temperatures, and time. Maximum swelling percentage of IPP-g-MMA (92%) was observed in 8 hours at60 ∘ C . The evidence of grafting was carried out by Fourier transform spectroscopy (FTIR), atomic force microscopy (AFM), and scanning electron microscopy (SEM) before and after grafting, respectively. The swelling pattern was characterized by two distinct stages, an initial diffusion-controlled fast swelling, followed by a subsequent slower process controlled by the relaxation of polymer fragments. Swelling chrematistics of IPP-g-MMA make it a potentially useful material.